Management of Experiential Learning in Arabic Language Education - Afasa, Amalia Nur; Mahmudi, Ihwan; Yasin, Agus; Salsabila, Nanda Azzah (Al-Hayat: Journal of Islamic Education, 2026)
Good management in Arabic language learning is crucial to ensure that experiential learning runs effectively and meets its objectives. This study aims to explore the management of experiential learning in enhancing Arabic speaking skills at Darussalam Gontor Modern Islamic Boarding School. The research employs a qualitative approach with a case study design, collecting data through observation, interviews, and documentation. This study tested data validity through triangulation and analysed the data using Creswell’s interactive model, including data reduction, display, and conclusion drawing. The findings reveal that experiential learning management at Gontor is implemented systematically through planning, organising, actuating, and controlling. Each stage supports students' active participation in Arabic-speaking practices inside and outside the classroom. This management approach effectively fosters a communicative environment that enhances students’ speaking fluency, confidence, and linguistic discipline. However, challenges remain in maintaining language consistency among all learners. The originality of this study lies in integrating experiential learning management with the pesantren’s language environment to strengthen speaking skills. The implications highlight the importance of structured management for sustaining language practice programs. Future studies should examine its application in other pesantren contexts or among learners with varying levels of Arabic language proficiency.